Understanding the self-templating of hierarchically porous carbon electrocatalysts using Group 2 coordination polymers. Issue 1 (14th April 2020) - Farber, Eliyahu M.; Ojha, Kasinath; Burshtein, Tomer Y.; Hasson, Lihi; Eisenberg, David
Abstract : Hierarchical porosity in carbon materials can be realized by self-templating: controlled pyrolysis of well-designed metal–organic precursors. Abstract : Self-templating of hierarchical porosity in carbon materials can be realized by the pyrolysis of well-designed metal–organic precursors. While this strategy is elegant and scalable, detailed mechanistic understanding of the self-templating process is lacking. We now report a systematic investigation of the microstructural evolution in porous carbons, including hierarchically micro-/meso-/macroporous materials with variable mesopore size. We focus on a homologous series of well-defined metal–organic coordination polymers, combining the highly abundant Group 2 ions (Mg 2+, Ca 2+, Sr 2+, Ba 2+ ) with a common ligand. To understand the role of the metal ion in directing the morphology of the ultimate N-doped carbons, we performed a detailed investigation using electron microscopy (HRSEM, HRTEM, EDS), N2 porosimetry, XRD, XPS and Raman spectroscopy. The rich morphological variations in the carbons determine their activity as metal-free electrocatalysts towards the oxygen reduction reaction. In particular, the reaction selectivity (2e − vs. 4e − pathways) is directed by competition between kinetics and mass transfer, due to confinement in mesopores.